Revision of the Western Palaearctic Diplazontinae (Hymenoptera, Ichneumonidae) - Klopfstein, Seraina (Zootaxa, 2014)
I revise the subfamily Diplazontinae to include 99 Western Palaearctic species, review morphological characters useful for species delimitation and identification, and clarify the status of some morphologically similar taxa using molecular approaches. Illustrated, dichotomous keys to the Western Palaearctic genera and species of the subfamily are presented, and the utility of the molecular markers CO1 and ITS2 for species delimitation in Diplazontinae is discussed. Seven new species are described, Diplazon flixi sp. nov., Diplazon nordicus sp. nov., Diplazon parvus sp. nov., Diplazon zetteli sp. nov., Eurytyloides umbrinus sp. nov., Sussaba roberti sp. nov., and Woldstedtius bauri sp. nov. The Nearctic Sussaba cultriformis (Ashmead), formerly a subspecies of Sussaba dorsalis (Holmgren), is raised to species rank. The following taxa are valid species and hereby removed from synonymy: Episemura ensata (Bauer), stat. rev.; Homotropus frontorius (Thunberg), stat. rev.; Syrphoctonus desvignesii (Marshall), stat. rev.; Syrphophilus scabriculus (Holmgren), stat. rev.; and Tymmophorus suspiciosus (Brischke), stat. rev. Nineteen new synonyms are established: Bioblapsis mallochi Rotheray of Bioblapsis cultiformis (Davis), syn. nov.; Bioblapsis tricincta Ashmead of Syrphophilus scabriculus (Holmgren), syn. nov.; Diplazon bachmaieri Diller of Diplazon angustus Dasch, syn. nov.; Diplazon fechteri Diller of Diplazon cascadensis Dasch, syn. nov.; Homocidus brevis Hedwig of Homotropus pictus (Gravenhorst); Homocidus rubiginosum Schmiedeknecht of Enizemum scutellare (Lange), syn. nov.; Homocidus simulans Stelfox of Homotropus collinus (Stelfox), syn. nov.; Homotropus crassicrus Thomson and Homotropus nudus Dasch of Homotropus dimidiatus (Schrank), syn. nov.; Homocidus asyntactus Schmiedeknecht of Homotropus crassicornis Thomson, syn. nov.; Homocidus subopacus Stelfox and Homotropus quadrangularis Dasch of Homotropus frontorius (Thunberg), syn. nov.; Homocidus impolitus Stelfox of Homotropus pallipes (Gravenhorst), syn. nov.; Homotropus incisus Thomson and Homotropus reflexus Morley of Homotropus pectoralis (Provancher), syn. nov.; Tryphon nigricornis Zetterstedt, a former synonym of H. dimidiatus Schrank, is a synonym of Homotropus pictus (Gravenhorst), syn. nov.; Homotropus fraudulentus Dasch and Homotropus neopulcher Horstmann of Syrphoctonus desvignesii (Marshall), syn. nov.; Homotropus eximius Habermehl of Syrphoctonus tarsatorius (Panzer), syn. nov. The following new combinations are established: Bioblapsis cultiformis (Davis), comb. nov.; Homotropus collinus (Stelfox), comb. nov.; Homotropus dimidiatus (Schrank), comb. nov.; Homotropus frontorius (Thunberg), comb. nov.; Homotropus pectoralis (Provancher), comb. nov.; Homotropus strigator (Fabricius), comb. nov.; Homotropus sundevalli (Holmgren), comb. nov. The present revision is the first comprehensive treatment of the Western Palaearctic Diplazontinae, provides the basis for taxonomic, faunistic, ecological and evolutionary studies in these hoverfly parasitoids, and exemplifies an integrative approach to systematics and taxonomy.